Erratum to: Measurement of [psi](2S) meson production in pp collisions at √s=7 TeV - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Dordei, Francesca; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Jäger, Andreas; Kreplin, Katharina; Krocker, Georg Alexander; Linn, Christian; Marks, Jörg; et al. (The European physical journal. C, Particles and fields, 2020)
This erratum corrects measurements of the prompt and secondary (from-b) psi (2S) production cross-sections in the forward region in pp collisions at root s = 7TeV. The original measurements were performed using data collected with the LHCb detector in 2010 and were published in the original article. Corrected results for prompt psi(2S) and psi(2S)from-b in the kinematic range pT(psi(2S)) < 16GeV/c and 2.0 < y(psi(2S)) < 4.5 are where the last uncertainty on the prompt cross-section is due to the unknown psi(2S) polarization. With the corrected psi (2S)-from-b cross-section the inclusive branching fraction is updated by B(b ->psi(2S) X) = (3.08 +/- 0.07(stat) +/- 0.36(syst) +/- 0.27(B)) x 10(-3).